The great catnapping - Ecton, Emily (Ecton, Emily, Great Pet Heist., 2024)
During a TV appearance at a supermarket opening, Walt and Princess Jubilee are catnapped, so the Strathmore pets take matters into their own hands to bring the two cats home.